Actions taken affecting lead time in the care pathway for low-priority patients with a suspected stroke: A critical incident study. (January 2022) - Wennman, Ingela; Carlström, Eric; Fridlund, Bengt; Wijk, Helle
Highlights: The care pathway for low-priority stroke patients suffers from time delays. There are several actions taken effecting the lead time. Staff affect the lead time individually and via interaction between departments. Collaboration and consensus on how to facilitate a smooth care pathway is needed. Abstract: Background: The time delay from alerted ambulance to arrival at the stroke unit is crucial for patients suffering a suspected stroke. This is a recognized problem why additional explorative knowledge regarding actions taken are needed. Aim: To explore actions taken by nurses that affect lead times in the care pathway from the alerted ambulance to the stroke unit, for low-priority patients suffering a suspected stroke. Method: The design of the study was explorative and descriptive and used a qualitative approach based on Critical Incident Technique (CIT). Twenty-two nurses involved in the stroke care pathway at an university hospital in western Sweden were interviewed about their actions that affected the lead time. Results: Actions undertaken affected lead time in the stroke care pathway for low-priority patients related to "promoting the care chain process" and "taking control of the situation". Conclusions: The staff within all parts of the care pathway affected the lead time, individually as well as via interaction between departments. This calls for the need of further collaboration and consensus concerning how to facilitate a smooth care pathway.